Otoritas hadis sirah sebagai referensi yuridis-dogmatis dalam Islam - Dzikri Nirwana (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
Muslims researchers make separation between legal traditions (ahadith al-ahkam) documented in theliterature traditions; and historical traditions (ahad ith al-sira) are summarized in the literature of classicalIslamic historiography. But it turns out in a number of Sirah literature, there are some traditions ofAhk am found. In contras, in the hadith literatures, there are also found historical tradition. From here,it can be stated that the tradition has three dimensions at once; historical dimension, categorized ashadith Sirah; juridical dimension, identified as hadith Ahk am; and historical and juridical dimension aswell. For this latter form, the hadith can be flexible and conditional, in the sense that when it is containedin the literature historiography, categorized as hadith Sirah, and vice versa, as contained in the Hadithliterature in the form of juridical -dogmatic,- it is categorized as a hadith al-Ahkam. Therefore, thehadith sira patterned in two functions; justification prophetic treatise (dala’ il Nabawiyya); and juridical -dogmatic arguments (dala’il diniyyah). These two functions are the implications of the concept ofimitation of the Prophet as an integral whole, because its realization as a model of humanity , philosophicallycould not limited by space and time. Life events and behaviors Nabawiyya being operatedfrom childhood until the prophetic, always maintained from disobedience (‘ismah) , in addition to alsoendowed a number of advantages , as a sign that he is a ‘candidate’ prophets and apostles (irhas)